Marine Archaeogeophysical Prospection of Roman Salapia Settlement (Puglia, Italy): Detecting Ancient Harbour Remains - Cocchi, L.; Stefanelli, P.; Carmisciano, C.; Caratori Tontini, F.; Taramaschi, L.; Cipriani, S. (Archaeological prospection, 2012)
ABSTRACT The Gulf of Manfredonia and the Tavoliere Plain have experienced intense human colonization since the neolithic times. There is past evidence in the study area of a Roman‐age settlement historically known as Salapia, probably located close to the salt‐production ponds. In particular, several portions of a partly submerged ancient pier‐like structure were found close to Torre Pietra town. This structure has been interpreted as a portion of a dragged‐ship channel that connected the town of Salapia to the sea. In this article we discuss the results of a high‐resolution geophysical prospecting of the Margherita di Savoia offshore archaeological site (Puglia, Italy). We collected magnetic gradiometric and bathymetric data to map the submerged remains of Salapia harbour. We found evidence of an offshore projection of a Torre Pietra pier‐like structure, identifying the direction of the ship channel and possibly the location of the harbour's defensive post. Copyright © 2012 John Wiley & Sons, Ltd.